2013
DOI: 10.1371/journal.pone.0054951
|View full text |Cite
|
Sign up to set email alerts
|

Disturbed Subjective Sleep in Chinese Females with Type 2 Diabetes on Insulin Therapy

Abstract: ObjectivesThe aim of this study is to investigate the prevalence and determine the possible risk factors of poor sleep quality in Chinese type 2 diabetes patients with insulin treatment.Methods140 type 2 diabetes patients with insulin treatments were enrolled in our study. General characteristics and laboratory testing such glycosylated hemoglobin A1c (HbA1c), fasting plasma glucose (FPG), post-prandial plasma glucose (PPG) were measured. Every patient completed Chinese version of Pittsburgh Sleep Quality Inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 27 publications
3
19
0
Order By: Relevance
“…However, a previous study among adults with type 1 diabetes found a similar prevalence of self-reported poor sleep quality (35%) [9]. Also, the rate of subjective poor sleep quality in type 2 diabetes found in our study (42%) falls near the 45-70% range that is typically reported in this group (e.g., [3][4][5]). Second, as we did not include a matched control group without diabetes, we cannot determine whether sleep impairments are more common in adults with diabetes compared to those without this condition.…”
Section: Strengths and Limitationssupporting
confidence: 74%
See 2 more Smart Citations
“…However, a previous study among adults with type 1 diabetes found a similar prevalence of self-reported poor sleep quality (35%) [9]. Also, the rate of subjective poor sleep quality in type 2 diabetes found in our study (42%) falls near the 45-70% range that is typically reported in this group (e.g., [3][4][5]). Second, as we did not include a matched control group without diabetes, we cannot determine whether sleep impairments are more common in adults with diabetes compared to those without this condition.…”
Section: Strengths and Limitationssupporting
confidence: 74%
“…Furthermore, quality indicators such as difficulties in initiating and maintaining sleep increase the risk for type 2 diabetes onset by 57% and 84%, respectively [2]. The rate of self-reported poor sleep quality in adults with diagnosed type 2 diabetes generally ranges between 45% and 70% (e.g., [3][4][5]), compared to 10-30% in the general population and elderly without diabetes [6][7][8]. However, most estimates in type 2 diabetes are based on studies with small sample sizes (typically, N < 150).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tsai et al (22) stressed the significant association between poor sleep and worse glycemic control among diabetic patients. Using PSQI >5 as a cutoff, Song et al (23) reported that the prevalence of poor sleep quality among diabetics was 49.3%. Lou et al (17) reported that the prevalence of poor sleep among diabetics was 33.6%.…”
Section: Discussion:-mentioning
confidence: 99%
“…Interestingly, after adjusting duration of DM, the relationship between sleep duration and worse glycemic control disappeared. The long duration of DM could be more likely to have comorbidities and these comorbidities may be a cause of shorter or longer sleep and also worse glycemic control (19, 20). When we selected subgroup of DM duration less than 5 yr, which might have no diabetic complications such as neuropathy, there was no association between sleep duration and glycemic control.…”
Section: Discussionmentioning
confidence: 99%